From hands-on to family-on: Task-Shifting manual therapy techniques in post-stroke neuroplasticity - A retrospective comparative analysis of the Cogni-Famille protocol. - Npochinto Moumeni, Ibrahim; Abdel-Nasser, Njikam Moumeni; Bristher Horlister, Tchuidjio Ketchogué; Temgoua, Michael; Mapoure, Yakouba Njankouo (Journal of Bodywork & Movement Therapies, 2026)
Manual therapy techniques have demonstrated efficacy in post-stroke rehabilitation through neuroplastic mechanisms, yet accessibility remains limited by specialist availability. Family-centered task-shifting approaches may democratize manual therapy delivery while amplifying therapeutic intensity. Objective: To evaluate the effectiveness of structured family training in manual therapy techniques for post-stroke recovery through the innovative Cogni-Famille protocol, with primary outcome measured by Montreal Cognitive Assessment (MoCA) score changes and functional independence (Barthel Index). Retrospective comparative cohort study analyzing 13 post-stroke patients receiving family-delivered manual therapy training (25-h structured program, March 2024–June 2025) versus 13 historical controls receiving conventional therapy (December 2022–January 2024). Significant improvements in MoCA scores (+5.8 ± 2.1 vs +2.1 ± 1.3 points, p < 0.001, effect size 2.1), functional independence (85 % vs 46 %, p = 0.02), Zarit caregiver burden reduction (−18.3 ± 4.7 vs −6.2 ± 3.1, p < 0.001), and Modified Ashworth Scale spasticity improvement (−2.1 ± 0.8 vs −0.7 ± 0.6, p < 0.001). Task-shifting model achieved 94 % family certification rate with zero serious adverse events. Cost reduction of 68 % (742€ vs 2310€, p < 0.001). Structured family training in manual therapy techniques achieves superior outcomes through neuroplastic amplification via intensive, culturally-adapted delivery. This model offers scalable solutions for global stroke rehabilitation while maintaining safety and therapeutic effectiveness.